The impact of time of neutering on weight gain and energy intake in female kittens. (15th May 2017) - Allaway, David; Gilham, Matthew; Colyer, Alison; Morris, Penelope J.
Abstract: Neutering is a risk factor for obesity in companion animals. In a study to determine the total energy requirements of kittens (15–52 weeks) the impact of neutering and age when neutered on intake and body weight (BW) was investigated. Females ( n 14), neutered when 19 (early neuter; EN) or 31 (conventional neuter; CN) weeks old ( n 7/group), were individually fed to maintain an ideal body condition score (BCS). EN kittens gained weight gradually whilst CN kittens' BW gain slowed from week 24, weighing less than EN kittens from week 30 with a reduced energy intake (kcal/kg BW 0·67 ) in weeks 24–32 ( P < 0·05). Following neutering, CN cats' BW and energy intake increased rapidly (energy intake CN > EN in weeks 36–40). Although EN required earlier diet restriction, acute hyperphagia and increased rate of BW gain following neutering were not observed. Earlier neutering may aid healthy weight management through growth when regulating intake to maintain an ideal BCS.